Genital skin diseases and their expression in sexual functionality - Gabriela Albu; Mircea Tampa; Maria Isabela Sarbu; Simona Roxana Georgescu (Journal of Mind and Medical Sciences)
Sexual functionality acts as an important function of the individual, acting both physically and mentally to create a state of well-being and permitting procreation. A large number of mucosal and cutaneous ailments may affect the genial areas in both males and females, generally leading to local symptoms that impede the sexual act. Genital diseases, sometimes even without impairing the sexual function, may still alter the dynamics just because of the enormous psychological impact that occurs in these situations. We aim to review main dermatological disorders that alter normal function of the genitalia, as well as their physical mechanism by which the sexual functionality is changed.